MENANAMKAN JIWA ENTREPRENEURSHIP YANG OPTIMIS DAN BERIMAN BAGI WARGA DI DESA JAGABAYA KHUSUSNYA KAUM DISABILITAS UNTUK KEHIDUPAN YANG HARMONIS DENGAN LINGKUNGAN DI SEKITARNYA - Munalar, Hj. Sri Siti; Nurhayati, Nurhayati; Syaukat, Mahmud; Fania, Frieda (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
When happiness is the dream of every human being, it is mandatory for the dreamer to make it happen. It is axiomatic that to achieve hope is to work for it until it is realized what it wants. Without effort, without moving towards are impossible to achieve goals. Inevitably, the residents of Jagabaya Village are also, in order to instill and foster an entrepreneurial spirit for the villagers, so we as lecturers of the Faculty of Law, Pamulang University participate in the field providing legal counseling regarding the importance of the role of Entrepreneurs in advancing UMKM and the Indonesian economy during this pandemic. in general, and in particular those based on the provisions of applicable norms. It is equally well known that every citizen has the same position, the same rights, the same role (according to his capacity) and who certainly gets a good life and is under the same protection in the eyes of the law. These achievements can be realized in the form of entrepreneurship as an effort to prosper themselves, to further improve the welfare of the nation. The ability to work, produce works or businesses with selling points and compete in the market is not only monopolized by a certain group of people, but belongs to all community components, including people with disabilities in Jagabaya village. The Government of Indonesia protects, respects, promotes, and fulfills the rights of persons with disabilities, with the legal umbrella being laws and regulations for the protection of persons with disabilities. Guarantees for all Indonesian citizens to be independent, independent and entrepreneurship to meet the needs of their lives and the general public have been clearly regulated in the constitution. someone who wants to be an entrepreneur. All of them need to be supported by experience, formal and informal education, as well as training and training that is useful for knowing one’s potential and burning the entrepreneurial spirit within. So, through the Tridharma Perguruan Tinggi program, we as law faculty lecturers who have different practical experience backgrounds, participate through legal counseling which is carried out simultaneously by several other PKM teams, in order to share knowledge and experience with community members in Jagabaya Village. We fill this activity by providing information and knowledge related to Entrepreneurship Science, sharing sessions with residents, exchanging experiences to add insight, and motivating residents to take on the role of being part of Indonesian UMKM. The output targets that will be produced are reporting through articles in electronic media to inform PKM activities that have taken place, as well as publishing journal outputs as a crystallization of this higher education tridharma activity.